Investigation of Dorsal Fin Effects on the Aerodynamic Performance of Inverted-V Empennage VTOL Unmanned Aerial Vehicle - Bramantya, Muhammad Agung; Nugroho, Gesang (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2025)
Unmanned Aerial Vehicles (UAVs) are becoming essential tools in precision agriculture, enabling real-time monitoring, improved land management, and more efficient use of resources. Among them, Vertical Takeoff and Landing (VTOL) UAVs are ideal for operating in confined and uneven agricultural terrains. However, UAVs equipped with inverted-V empennages suffer from aerodynamic drawbacks, including directional instability and adverse yaw under sideslip conditions. This paper advances the state of the art by optimizing the aerodynamic performance of inverted-V tail configurations through the integration of a dorsal fin. Using Computational Fluid Dynamics (CFD), we assess multiple dorsal fin designs on a UAV platform with a maximum takeoff weight of 10 kg, 2 kg payload, 2-hour endurance, 10 m/s stall speed, and a 5 km² operational range. We analyze key aerodynamic metrics—lift and drag coefficients, lift-to-drag ratio, yaw moment coefficient—as well as flow behavior via pressure contours and vorticity plots. Results confirm that sideslip angles degrade aerodynamic efficiency, but a properly designed dorsal fin, particularly variation 2, significantly reduces adverse yaw at higher angles of attack and sideslip. This modification enhances UAV stability and flight performance, marking a meaningful improvement in VTOL UAV design for agricultural applications.